2021
DOI: 10.1002/jum.15727
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasound for Detecting Gastric or Duodenal Ulcers in Pediatric Patients

Abstract: Objective-Direct ultrasound imaging findings alone have low sensitivity for diagnosing duodenal (65%) and gastric ulcers (40%). This retrospective study evaluated the efficiency of ultrasound in detecting gastric/duodenal ulcers in pediatric patients through direct and indirect findings.Methods-We evaluated 244 children who underwent ultrasound and subsequent endoscopy within 4 weeks for direct and indirect imaging findings indicative of gastric/duodenal ulcers. Positive direct imaging findings revealed gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…In case 3, inflammatory change was noted in the mesentery and high echogenicity around the mesentery was detected by US. This finding was reported to indicate inflammation [19]. In this case, however, US did not show a bowel wall thickness of >3 mm or loss of the wall stratification and VEO-IBD was diagnosed based on the endoscopic and pathological findings.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In case 3, inflammatory change was noted in the mesentery and high echogenicity around the mesentery was detected by US. This finding was reported to indicate inflammation [19]. In this case, however, US did not show a bowel wall thickness of >3 mm or loss of the wall stratification and VEO-IBD was diagnosed based on the endoscopic and pathological findings.…”
Section: Discussionmentioning
confidence: 56%
“…Although not specific to VEO-IBD, the following factors were important indicators of an IBD diagnosis: 1) bowel wall thickness and its stratification and 2) the distribution of inflammation [15][16][17][18]. Regarding the bowel wall thickness and its stratification, the cut-off value of bowel wall thickness was reported to be ≤3 mm (2-2.5 mm) [15][16][17][18][19][20][21][22][23][24]. Pathological inflammation mainly involves the mucosa and superficial submucosa in UC and all bowel wall layers from the mucosa to the serosa in CD [14].…”
Section: Discussionmentioning
confidence: 99%
“…Transabdominal ultrasonography is an effective method for detecting peptic ulcer in low-weight children[ 20 ]. Therefore, sonographers should carefully evaluate indirect findings around the stomach or duodenum[ 21 ]. Fifteen cases were diagnosed by gastrointestinal CEUS, the diagnostic accuracy was 88.2% (15/17), and the coincidence rate was 95.3% (41/43).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, CT scan is less sensitive for diagnosing gastroduodenal ulcers ( 17 ). Hosokawa et al showed that not only direct findings including thickening of the gastrointestinal wall and ulcers but also indirect findings such as hyperintense fatty tissue around ulcers and lymph nodes are useful in pediatric patients with gastric and duodenal ulcers ( 14 ). In this study, 15 of 17 children had abnormal AUS findings that were correlated with the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, none of the previously mentioned procedures were performed in this study. AUS is a minimally invasive and simple examination and has a high detection rate for gastrointestinal lesions in children with a thin subcutaneous fat (14)(15)(16). By contrast, CT scan is less sensitive for diagnosing gastroduodenal ulcers (17).…”
Section: Discussionmentioning
confidence: 99%